Red sintered body and its manufacturing method
By using trivalent germanium, aluminum, yttrium and other elements in zirconium oxide ceramics, controlling the component ratio and crystal structure, the problem of insufficient color of existing zirconium oxide ceramics is solved, and the display of bright red tones and color stability is achieved.
Patent Information
- Application Number
- JP2024128929
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-29
- Filing Date
- 2024-08-05
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-08-05
AI Technical Summary
When used in appearance components and external electronic equipment, the color of existing zirconium oxide ceramics is not pure enough, especially in red tones, which are prone to change color due to changes in thickness, and are weaker in small or thin members.
Using trivalent germanium as the coloring component, combined with elements such as aluminum and yttrium, a zirconium oxide ceramic that produces a red tone based on reflected light was prepared by controlling the component ratio and crystal structure.
It realizes the bright red zirconium oxide ceramics in sunlight, and the color performance is stable and not affected by thickness changes. It is suitable for external use of various appearance components and electronic equipment.
Smart Images

Figure 0007662099000001 
Figure 0007662099000002 
Figure 0007662099000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body containing zirconia as a main component and exhibiting a red color, and a method for producing the same. [Background technology]
[0002] Zirconia sintered bodies containing coloring components, so-called colored zirconia sintered bodies, are in demand for use in decorative materials and exterior parts of electronic equipment. Among these, cerium oxide (CeO 2 ) zirconia sintered bodies are attracting attention.
[0003] For example, 0.5 mol% or more of CeO 2 A zirconia sintered body made of tetragonal zirconia obtained by reducing cerium has been reported as a red sintered body (Patent Document 1). 2 O 3 A translucent zirconia sintered body made of cubic crystals containing cerium oxide and neodymium oxide has been reported (Patent Document 2). Compared with the red zirconia sintered bodies reported so far, the zirconia sintered body according to Patent Document 2 exhibits a more reddish color tone. Furthermore, Patent Document 3 reports that the difference in reflectance for light wavelengths of 590 nm and 630 nm increases when the zirconia sintered body contains cerium oxide and neodymium oxide as coloring components and is subjected to a reduction treatment.
[0004] On the other hand, Patent Document 4 reports that in a red zirconia sintered body containing cerium oxide as a coloring component, the zirconia sintered body exhibits uniform coloring by coexisting an aluminum compound, and there is no change in color tone depending on the thickness of the sintered body. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 62-83366 [Patent Document 2] JP 2011-207745 A [Patent Document 3] JP 2017-132647 A [Patent Document 4] JP 2017-75086 A Summary of the Invention [Problem to be solved by the invention]
[0006] The zirconia sintered body of Patent Document 2 has very high translucency, and its coloring is due to transmitted light. The coloring due to transmitted light is a transparent color tone like colored glass, and the color tone changes significantly depending on the thickness of the sintered body. Therefore, when this zirconia sintered body is used as a small or thin member, the coloring becomes very weak.
[0007] In contrast, the sintered bodies of Patent Documents 1 and 3 show a stable color regardless of the size of the member, since the color is mainly due to the reflected light on the surface of the sintered body. The zirconia sintered bodies containing cerium oxide reported in Patent Document 1 all show a reddish color tone. However, these colors are intermediate colors between orange and red, between brown and red, or between black and red, and are not pure red. In addition, the zirconia sintered body containing cerium oxide and neodymium oxide disclosed in Patent Document 3 is a sintered body in which the reddish color is enhanced by the inclusion of neodymium oxide, but still has an intermediate color between orange and red. I did.
[0008] The color tone of the zirconia sintered body of Patent Document 4 was an intermediate color between orange and red, and did not have the aesthetic appeal of a pure red color.
[0009] In view of these problems, the present disclosure aims to provide at least one of a zirconia sintered body that exhibits a red color mainly due to reflected light based on the color development of trivalent cerium and that exhibits a vivid red color in daylight, and a method for producing the same. [Means for solving the problem]
[0010] The present inventors have investigated a zirconia sintered body that contains trivalent cerium as a coloring component and that exhibits a red color when reflected light is applied. As a result, they have found that a zirconia sintered body containing trivalent cerium as a coloring component exhibits a vivid red color in daylight by containing aluminum and a specific color-matching element.
[0011] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] Contains cerium, aluminum, yttrium, and color-matching elements; CEO 2 The converted cerium content is 1.5 mol% or more and 6.0 mol% or less, Al 2 O 3 The converted aluminum content is 0.05 mol% or more and 4.0 mol% or less, Y 2 O 3 The converted yttrium content is 2.0 mol% or more and 6.0 mol% or less, and The content of the color-changing element calculated as an oxide is more than 0 mol% and not more than 4.0 mol%, The cerium is trivalent cerium (Ce 3+ ), The color-changing element is at least one element selected from the group consisting of rare earth elements other than yttrium and cerium and alkaline earth metal elements, and Tetravalent zirconium (Zr 4+ ) the ratio of the ionic radius of the color-changing element to the ionic radius of the color-changing element is more than 1.00 and is 1.60 or less; Zirconia sintered body. [2] The sintered body according to [1], wherein the zirconia has a crystal structure including tetragonal and cubic crystals. [3] The sintered body according to [1] or [2], wherein the color-tuning element is one or more selected from the group consisting of calcium, magnesium, erbium, holmium, dysprosium, terbium, gadolinium, europium, samarium, neodymium, praseodymium, and lanthanum. [4] The sintered body according to any one of [1] to [3], wherein the ratio of the ionic radii of the color-tuning elements is greater than 1.33 and not greater than 1.40. [5] L * a * b * In the color system, hue b * Hue a * The ratio (a * / b * ) is 2.0≦(a * / b * The sintered body according to any one of [1] to [4] above, [6] Reflectance at 700 nm (R 700 ) and the reflectance for light with a wavelength of 600 nm (R 600 ) ratio (R 700 / R 600 ) is 2.4 or less (R 700 / R 600 The sintered body according to any one of [1] to [5] above, [7] The sintered body according to any one of [1] to [6], wherein the ratio of the peak top height at 2θ=37.0±0.3 to the peak top height at 2θ=30.0±0.3 in an XRD pattern is 0.005 or less. [8] A method for producing a zirconia-based composition comprising the steps of: CEO 2 The converted cerium content is 1.5 mol% or more and 6.0 mol% or less, Al 2 O 3 The converted aluminum content is 0.05 mol% or more and 4.0 mol% or less, Y 2 O 3 The converted yttrium content is 2.0 mol% or more and 6.0 mol% or less, and The content of the color-changing element calculated as an oxide is more than 0 mol% and not more than 4.0 mol%, The color-tuning element source is a compound containing at least one element selected from the group consisting of a rare earth element other than yttrium and cerium and an alkaline earth metal element, and Tetravalent zirconium (Zr 4+ ) has an ionic radius of more than 1.0 and not more than 1.6. [9] A method for producing a sintered body according to any one of [1] to [7] above, comprising: a molding step of molding the powder composition according to [8] above to obtain a molded body; a step of sintering the molded body under atmospheric pressure to obtain a primary sintered body; and a secondary sintering step of sintering the primary sintered body in a reducing atmosphere. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide at least one of a zirconia sintered body that exhibits a red color mainly due to reflected light based on the color development of trivalent cerium and that exhibits a vivid red color in daylight, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The sintered body of the present disclosure will be described below with reference to an example embodiment. The terms used in this embodiment are as follows.
[0014] The term "composition" refers to a substance having a certain composition, and includes, for example, one or more selected from the group consisting of powder, granules, molded body, calcined body, and sintered body. The term "zirconia composition" refers to a composition essentially consisting of zirconia, and further, a composition having zirconia as a matrix (base material).
[0015] A "powder" is a composition that is an aggregate of powder particles and has flowability. A "zirconia powder" is a powder that is essentially made of zirconia, or a powder that has zirconia as a matrix (base material). A "powder composition" is a composition that is composed of powders with different characteristics, and in particular, a composition that contains powders with different compositions.
[0016] A "molded body" is a composition having a certain shape composed of powder particles aggregated by physical force, and in particular, a composition in a state in which no heat treatment has been performed after the shape has been imparted (e.g., after molding). A "zirconia molded body" is a molded body essentially made of zirconia, and further, a molded body having zirconia as a matrix (base material).
[0017] A "sintered body" is a composition having a certain shape composed of crystal grains, and is a composition in a state in which it has been heat-treated at a temperature equal to or higher than the sintering temperature. A "zirconia sintered body" is a sintered body essentially made of zirconia, and further, a sintered body having zirconia as a matrix (base material).
[0018] The term "stabilizing element" refers to an element that has the function of stabilizing the crystal phase of zirconia by dissolving in the zirconia.
[0019] The "BET specific surface area" may be measured by a BET multipoint method (5 points) using nitrogen as the adsorption gas in accordance with JIS R 1626. Specific measurement conditions for the BET specific surface area include the following conditions.
[0020] Adsorption medium:N 2 Adsorption temperature: -196℃ Pretreatment conditions: Degassing in air at 250℃ for 1 hour or more The BET specific surface area can be measured using a common device (for example, Tristar II 3202, manufactured by Shimadzu Corporation).
[0021] "Average particle size" refers to the particle size equivalent to D50 (median size) of the volumetric particle size distribution obtained by the laser diffraction / scattering method using a general particle size distribution measuring device (e.g., device name: MT-3100II, manufactured by Microtrack Bell). Specific measurement conditions include the following:
[0022] Measurement range: 0.01~2000μm Particle refractive index: 2.17 Particle permeability: permeation Particle shape: non-spherical Solvent refractive index: 1.333 "Normal pressure sintering" is a method of sintering by heating the material to be sintered (such as a compact or calcined body) without applying an external force. [Sintered body] This embodiment contains cerium, aluminum, yttrium, and a color-matching element, CEO 2 The converted cerium content is 1.5 mol% or more and 6.0 mol% or less, Al 2 O 3 The converted aluminum content is 0.05 mol% or more and 4.0 mol% or less, Y 2 O 3 The converted yttrium content is 2.0 mol% or more and 6.0 mol% or less, and The content of the color-changing element calculated as an oxide is more than 0 mol% and not more than 4.0 mol%, The cerium is trivalent cerium (Ce 3+ ), The color-changing element is at least one element selected from the group consisting of rare earth elements other than yttrium and cerium and alkaline earth metal elements, and Tetravalent zirconium (Zr 4+ The present invention relates to a zirconia sintered body, in which the ratio of the ionic radius of the color-tuning element to the ionic radius of trivalent cerium is more than 1.00 and not more than 1.60. With this constitution, a zirconia sintered body that exhibits a red color due to the color development of trivalent cerium and also exhibits a vivid red color under daylight, that is, a so-called red zirconia sintered body, is obtained.
[0023] The sintered body of the present embodiment contains cerium, aluminum, yttrium, and a color-tuning element. In the sintered body of the present embodiment, it is preferable that the cerium, yttrium, and the color-tuning element are solid-dissolved in zirconia. On the other hand, it is preferable that the aluminum is contained as alumina particles.
[0024] The sintered body of this embodiment is Y2 O 3 The converted yttrium content (hereinafter, simply referred to as "yttrium content") is 2.0 mol% or more and 6.0 mol% or less. If the yttrium content is less than 2.0 mol%, defects are likely to occur during production, and sintered bodies cannot be obtained stably. On the other hand, if the yttrium content exceeds 6.0 mol%, the strength decreases.
[0025] The yttrium content of the sintered body of this embodiment may be 2.0 mol% or more, 2.2 mol% or more, 2.4 mol% or more, or 2.5 mol% or more, and 6.0 mol% or less, 5.5 mol% or less, 5.0 mol% or less, 4.5 mol% or less, or 4.0 mol% or less. Preferred yttrium contents include, for example, 2.0 mol% to 6.0 mol%, 2.2 mol% to 5.5 mol%, 2.4 mol% to 5.0 mol%, 2.4 mol% to 4.5 mol%, or 2.5 mol% to 4.0 mol%.
[0026] The sintered body of this embodiment is CeO 2 The converted cerium content (hereinafter simply referred to as "cerium content") is 1.5 mol% or more and 6.0 mol% or less. If the cerium content is less than 1.5 mol%, a reddish color cannot be obtained. On the other hand, if the cerium content exceeds 6.0 mol%, the sintered body will take on a blackish color, making it impossible to obtain a bright red sintered body. The cerium content may be 1.5 mol% or more, 1.8 mol% or more, 2.0 mol% or more, or 2.2 mol% or more, and 6.0 mol% or less, 5.5 mol% or less, 5.0 mol% or less, 4.5 mol% or less, or 4.0 mol% or less. Preferred cerium contents include, for example, 1.5 mol% or more and 6.0 mol% or less, 1.8 mol% or more and 5.5 mol% or less, 2.0 mol% or more and 5.0 mol% or less, 2.0 mol% or more and 4.5 mol% or less, 2.0 mol% or more and 4.0 mol% or less, or 2.2 mol% or more and 4.0 mol% or less.
[0027] The cerium contained in the sintered body of the present embodiment is at least trivalent cerium (Ce3+ ). The inclusion of trivalent cerium causes the sintered body to exhibit a red color. The more trivalent cerium there is, the more likely the zirconia sintered body will have a reddish color tone. Therefore, the sintered body of this embodiment preferably contains a large amount of trivalent cerium, and the molar ratio of trivalent cerium in the cerium contained in the sintered body is preferably 50 mol% or more, 60 mol% or more, 70 mol% or more, or 80 mol% or more, and is preferably 100 mol% or less. Specific examples of the molar ratio of trivalent cerium include 50 mol% or more and 100 mol% or less, 60 mol% or more and 100 mol% or less, 70 mol% or more and 100 mol% or less, or 80 mol% or more and 100 mol% or less.
[0028] In this embodiment, the molar ratio of trivalent cerium in cerium can be determined from the X-ray absorption near edge fine structure spectrum (hereinafter also referred to as "XANES spectrum") at the Ce-L3 absorption edge. 3+ ) and tetravalent cerium (Ce 4+ ) The XANES spectrum of each standard sample is measured, and the pattern fitting of this and the XANES spectrum of the measured sample is performed to calculate the molar ratio of trivalent cerium in the cerium contained in the sintered body. The standard sample is a sample in which trivalent cerium is CeF 3 and tetravalent cerium is CeO 2 XANES spectra can be measured by performing background processing of X-ray absorption fine structure spectra (hereinafter also referred to as "XAFS spectra") measured at a general synchrotron radiation facility such as SPring-8 using an analysis program (for example, product name: Demeter, manufactured by Bruce Ravel). Pattern fitting can be performed using the above-mentioned analysis program.
[0029] The sintered body of this embodiment is Al 2 O 3The converted aluminum content (hereinafter, simply referred to as "aluminum content") is 0.05 mol% or more and 4.0 mol% or less. When the aluminum content is less than 0.05 mol%, the color tone is strong orange. On the other hand, when the aluminum content exceeds 4.0 mol%, the particles of the aluminum compound precipitated in the sintered body excessively reflect the incident light, so that the sintered body has an orange color tone. The aluminum content may be 0.05 mol% or more, more than 0.05 mol%, 0.08 mol% or more, or 0.1 mol% or more, and may be 4.0 mol% or less, 3.5 mol% or less, or 3.0 mol% or less. Preferred aluminum contents include, for example, 0.05 mol% or more and 4.0 mol% or less, more than 0.05 mol% and 4.0 mol% or less, 0.08 mol% or more and 3.5 mol% or less, or 0.1 mol% or more and 3.0 mol% or less.
[0030] The color-tuning element contained in the sintered body of the present embodiment is at least one element selected from the group consisting of rare earth elements other than yttrium and cerium, and alkaline earth metal elements, and further, tetravalent zirconium (Zr 4+ The ratio of the ionic radius of the color-changing element to the ionic radius of the color-changing element (hereinafter also referred to as "ionic radius ratio") is more than 1.0 and not more than 1.6. Specific examples of the color-changing element include one or more selected from the group consisting of calcium (Ca), magnesium (Mg), strontium (Sr), scandium (Sc), lutetium (Lu), ytterbium (Yb), thulium (Tm), erbium (Er), holmium (Ho), dysprosium (Dy), terbium (Tb), gadolinium (Gd), europium (Eu), samarium (Sm), neodymium (Nd), praseodymium (Pr), and lanthanum (La). Preferably, the element is one or more selected from the group consisting of calcium, magnesium, erbium, gadolinium, europium, samarium, neodymium, praseodymium, and lanthanum, more preferably one or more selected from the group consisting of calcium, magnesium, erbium, gadolinium, europium, neodymium, and lanthanum, even more preferably at least one of neodymium and lanthanum, even more preferably including lanthanum, and even more preferably lanthanum.
[0031] If an element with an ionic radius ratio of 1.0 or less is included, the color tone of the resulting sintered body will be dark red or brown, and will not exhibit a vivid red color. On the other hand, elements with an ionic radius ratio of more than 1.6 are difficult to dissolve in zirconia, and cannot exhibit a vivid red color in daylight. One of the reasons why the inclusion of an element with such a specific ionic radius ratio results in a vivid red color in daylight is the presence of Ce dissolved in zirconia. 3+ It is considered that the electronic structure of the color-changing element is changed. The color-changing element preferably has an ionic radius ratio of more than 1.0, 1.04 or more, 1.1 or more, 1.2 or more, or more than 1.33, and 1.60 or less, 1.50 or less, 1.40 or less, or 1.38 or less. The ionic radius ratio may be more than 1.00 and 1.60 or less, 1.04 or more and 1.50 or less, 1.10 or more and 1.40 or less, 1.20 or more and 1.38 or less, more than 1.33 and 1.40 or less, or more than 1.33 and 1.38 or less. * / b * and R 700 / R 600 Therefore, the ionic radius ratio of the color-matching elements is preferably more than 1.33 and not more than 1.40, and more preferably more than 1.33 and not more than 1.38.
[0032] The ionic radius ratio in this embodiment can be calculated by rounding off the ionic radius reported by Shannon (Acta. Crystallogr., A32, 751-67 (1976)) to two decimal places, and using the resulting value, according to the following formula:
[0033] [Ionic radius ratio] = [Ionic radius of element] / [Tetravalent zirconium (Zr 4+ ) ionic radius] The ionic radius of an element is the radius of an 8-coordinated ion, the valence of rare earth elements is trivalent, and the valence of group 2 elements is divalent. The ionic radius of a specific element is 1.12 Å (Ca 2+ ), 0.89Å(Mg 2+ ), 1.26Å(Sr 2+ ), 0.87Å(Sc 3+ ), 0.98Å(Lu 3+), 0.99Å(Yb 3+ ), 0.99Å(Tm 3+ ), 1.00Å(Er 3+ ), 1.02Å(Ho 3+ ), 1.03Å(Dy 3+ ), 1.04Å(Tb 3+ ), 1.05Å(Gd 3+ ), 1.07Å(Eu 3+ ), 1.08Å(Sm 3+ ), 1.11Å(Nd 3+ ), 1.13Å(Pr 3+ ), 1.16Å(La 3+ ), and 0.84Å (Zr 4+ ) are mentioned.
[0034] The ionic radius ratio is 1.33 for calcium (Ca 2+ / Zr 4+ ), and magnesium is 1.06 (Mg 2+ / Zr 4+ ), and strontium is 1.50 (Sr 2+ / Zr 4+ ), and scandium is 1.04 (Sc 3+ / Zr 4+ ), and lutetium is 1.17 (Lu 3+ / Zr 4+ ), and ytterbium is 1.18 (Yb 3+ / Zr 4+ ), thulium is 1.18 (Tm 3+ / Zr 4+ ), erbium is 1.19 (Er 3+ / Zr 4+ ), and holmium is 1.21 (Ho 3+ / Zr 4+ ), dysprosium is 1.23 (Dy 3+ / Zr 4+ ), and terbium is 1.24 (Tb 3+ / Zr 4+ ), and gadolinium is 1.25 (Gd 3+ / Zr 4+ ), and europium is 1.27 (Eu 3+ / Zr 4+ ), samarium is 1.29 (Sm 3+ / Zr 4+ ), neodymium is 1.32 (Nd3+ / Zr 4+ ), praseodymium is 1.35 (Pr 3+ / Zr 4+ ), and lanthanum is 1.38 (La 3+ / Zr 4+ ).
[0035] The sintered body of this embodiment has a content of the color-tuning element calculated as an oxide (hereinafter, simply referred to as "color-tuning element content") of more than 0 mol% and not more than 4.0 mol%. When the color-tuning element content is 0 mol%, that is, when the color-tuning element is not contained, the color tone becomes strong orange, and when the color-tuning element content exceeds 4.0 mol%, the strength of the sintered body decreases, which is not preferable. When the color-tuning element content exceeds 4.0 mol%, the sintered body becomes strong orange and does not show a vivid red color. This is considered to be due to the formation of a dispersed phase containing the color-tuning element in the sintered body.
[0036] The color-matching element content of the sintered body of this embodiment is preferably more than 0 mol%, 0.2 mol% or more, 0.3 mol% or more, 0.5 mol% or more, or 0.8 mol% or more, and 4.0 mol% or less, 3.0 mol% or less, 2.5 mol% or less, or 2.0 mol% or less. As a combination of these upper and lower limits, the color-matching element content is preferably more than 0 mol% and 4.0 mol% or less, 0.2 mol% or more and 3.0 mol% or less, 0.3 mol% or more and 2.5 mol% or less, 0.5 mol% or more and 2.5 mol% or less, or 0.5 mol% or more and 2.0 mol% or less. For example, in a sintered body containing cerium, aluminum, yttrium, and calcium (Ca) as a color-matching element, the yttrium content [mol%] is 2 Converted zirconium and Y 2 O 3 Y for the total converted yttrium 2 O 3 The converted molar percentage of yttrium [mol%] is {Y 2 O 3 [mol] / (ZrO 2 +Y 2 O 3The cerium content [mol%] in the sintered body is calculated by ZrO 2 Converted zirconium, Y 2 O 3 Converted yttrium, CeO 2 Cerium, oxide-converted color-matching elements, and Al 2 O 3 CeO relative to the total converted aluminum 2 The converted molar percentage of cerium [mol%] is {CeO 2 [mol] / (ZrO 2 +Y 2 O 3 +CeO 2 +CaO+Al 2 O 3 The aluminum content [mol%] in the sintered body is calculated by the formula: ZrO 2 Converted zirconium, Y 2 O 3 Converted yttrium, CeO 2 Cerium, oxide-converted color-matching elements, and Al 2 O 3 Al relative to the total converted aluminum 2 O 3 The converted aluminum mole fraction [mol%] is {Al 2 O 3 [mol] / (ZrO 2 +Y 2 O 3 +CeO 2 +CaO+Al 2 O 3 The color-tuning element content [mol%] in the sintered body is calculated by ZrO 2 Converted zirconium, Y 2 O 3 Converted yttrium, CeO 2 Cerium (calculated as CaO), calcium (calculated as CaO), and Al 2 O 3 The molar ratio [mol%] of calcium converted to CaO to the total of aluminum converted to ZrO 2 +Y2 O 3 +CeO 2 +CaO+Al 2 O 3 )[mol]}×100.
[0037] When the color-matching element contains magnesium, the sintered body contains a spinel compound of aluminum and magnesium (MgAl 2 O 4 (hereinafter, simply referred to as "spinel compound"). When magnesium is contained, the color of the sintered body tends to approach orange. Therefore, the sintered body of the present embodiment preferably does not contain a spinel compound. In order to suppress the formation of a spinel compound, when the color-tuning element contains magnesium, the magnesium content is preferably low, and is preferably 2.5 mol % or less or 2.0 mol % or less.
[0038] In the sintered body of this embodiment, the color-tuning element is preferably dissolved in zirconia. The dissolution of the color-tuning element in zirconia can be confirmed by the shift of the XRD peak corresponding to the cubic (400) plane to the lower angle side. The XRD peak corresponding to the cubic (400) plane is a peak having a peak top at 2θ=73.9±0.9° in the XRD pattern measured using CuKα radiation as a radiation source.
[0039] A preferred range of the peak top of the XRD peak corresponding to the cubic (400) plane of the sintered body of this embodiment is 2θ=73.0° or more and 73.9° or less, further 2θ=73.1° or more and 73.8° or less, and even further 2θ=73.1° or more and 73.7° or less, in an XRD pattern measured using a CuKα radiation source.
[0040] The sintered body of the present embodiment preferably does not contain impurities. 2 ) and other inevitable impurities, and impurities may be contained within a range that does not impair the effects of the present embodiment. In the present embodiment, in calculating values derived from the composition, such as density, hafnia may be regarded as zirconia.
[0041] In addition, the sintered body of the present embodiment preferably does not contain a spinel compound. 2 O 4 The presence of a spinel compound may be evaluated based on the ratio of the peak height of an XRD peak having a peak top at 2θ=37.0±0.3 to the peak height of an XRD peak having a peak top at 2θ=30.0±0.3 in an XRD pattern (hereinafter also referred to as the "spinel ratio"). In this embodiment, a spinel ratio of 0.005 or less, or even 0.004 or less, may be used to determine that a spinel compound is not contained.
[0042] The XRD pattern can be measured by a general X-ray diffraction device (device name: Ultima IV, manufactured by RIGAKU Corporation). The measurement conditions are as follows.
[0043] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ=26°~76° Acceleration voltage / current: 40mA / 40kV Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm After the measurement under the above measurement conditions, the analysis can be performed using the analysis program attached to the X-ray diffraction device (program name: Integrated Powder X-ray Analysis Software PDXL Ver. 2.2, manufactured by RIGAKU Corporation). The analysis conditions include the following conditions.
[0044] Peak shape: Split pseudo-Voigt function Background processing: Straight lines connecting endpoints In the sintered body of the present embodiment, the zirconia preferably contains tetragonal and cubic crystals in its crystal structure, and may be composed of tetragonal and cubic crystals, as well as monoclinic crystals.
[0045] The cubic phase ratio is a value calculated from the XRD pattern of the surface of the sintered body by the following formula.
[0046] f c =[I c (400)] / [I t (400)+I t (004)+I c (400)] In the above formula, f c is the cubic phase fraction, I c (400) is the surface intensity of the cubic (400) plane, I t (004) is the surface intensity of the tetragonal (004) plane, and I t (400) is the area intensity of the tetragonal (400) plane. The cubic crystal ratio of the sintered body of this embodiment can be, for example, 15% or more, 20% or more, 25% or more, or 30% or more, and 70% or less, 65% or less, or 60% or less. As a combination of these upper and lower limits, the cubic crystal ratio is preferably 15% or more and 70% or less, 20% or more and 65% or less, 25% or more and 60% or less, or 30% or more and 60% or less.
[0047] The XRD pattern and the area intensity of each crystal plane may be determined in the same manner as described above.
[0048] The XRD peaks corresponding to each crystal plane measured in the above-mentioned XRD measurement have peak tops at the following 2θ, and are considered to be peaks originating from the tetragonal (004) plane, cubic (400) plane, and tetragonal (400) plane, from the low angle side to the high angle side.
[0049] XRD peak corresponding to tetragonal (004) plane: 2θ=72.9±0.4° XRD peak corresponding to cubic (400) plane: 2θ=73.9±0.9° XRD peak corresponding to tetragonal (400) plane: 2θ=74.3±0.4° The sintered body of this embodiment is a zirconia sintered body that exhibits red color (hereinafter, also referred to as a "red zirconia sintered body"), and exhibits a vivid red color especially under daylight. The vivid red color tone is L * a * b * In the color system, hue b * Hue a * The ratio of (hereinafter, "a * / b * ") is 2.0≦a * / b * The following points can be mentioned.
[0050] The sintered body of this embodiment is * / b * is 2.0≦a * / b * By satisfying the above condition, the color tone will be emphasized reddish compared to yellowish. * / b * is preferably 2.0 or more, more preferably 2.1 or more, and is 4.0 or less, more preferably 3.5 or less.
[0051] The sintered body of the present embodiment has a vivid red color tone, * a * b * Lightness L in the color system * is between 40 and 60, and hue a * is 10≦a * ≦30 and hue b * b ≤ 3 * The more preferable color tone is the lightness L * is between 45 and 55, and hue a * is 15≦a * ≦30 and hue b * b ≤ 3 * ≦10.
[0052] In this embodiment, the color tone can be measured by a method conforming to the JIS Z8722 method, and can be measured under the following conditions using a general spectrophotometer (for example, CM-700d, manufactured by Konica Minolta).
[0053] Light source: D65 light source Viewing angle: 10° Measurement method: SCI Background: Black Measurement sample: (sample thickness) 2.4±0.1mm (Measured surface roughness) Ra≦0.02μm Lightness L * The higher the value, the brighter the color tone will be, and vice versa. * The smaller the hue, the darker the color. * indicates red to green tones, and a * The higher the value, the stronger the red tone, and the lower the value, the stronger the green tone. * The value indicates the yellow to blue tone, and b * The higher the value, the stronger the yellow tone, and * The lower the value, the stronger the blue tone.
[0054] Since the vivid red coloring is likely to become stronger, the reflectance of the sintered body of this embodiment to light with a wavelength of 700 nm (hereinafter referred to as "R 700 It is preferable that R is 40% or more, 45% or more, or 50% or more, and 90% or less, 85% or less, or 80% or less. 700 is preferably 40% or more and 90% or less, 45% or more and 85% or less, or 50% or more and 80% or less. In addition, the orange color tone is suppressed and a more vivid red color is easily exhibited, so that the reflectance of the sintered body of this embodiment with respect to light having a wavelength of 600 nm (hereinafter referred to as "R 600 " is also called. ) is preferably 30% or less, or 25% or less. The lower limit can be 10% or more, or 15% or more. As a combination of these upper and lower limits, R 600 is preferably 10% or more and 30% or less, 10% or more and 25% or less, or 15% or more and 25% or less.
[0055] Usually, R 700 When R is high, the reflectance for light of the surrounding wavelengths is high. However, by containing aluminum and a color-tuning element in the above-mentioned content, the wavelength of light absorbed by the sintered body changes. 700 Despite the high 600 As a result, the sintered body of this embodiment exhibits a more vivid red color under daylight. 600 R 700 The ratio of 700 / R 600 " is also referred to as ". ") is preferably 2.4 or more or 2.5 or more, and may be 3.5 or less or 3.3 or less. 700 / R 600 The combination of the upper and lower limits of " is preferably 2.4 or more and 3.5 or less, and more preferably 2.5 or more and 3.3 or less.
[0056] The reflectance can be determined from the diffuse reflectance spectrum measured under the following conditions using an ultraviolet-visible-near infrared spectrophotometer (e.g., V-650, manufactured by JASCO Corporation) equipped with an integrating sphere unit (e.g., ILV-724, manufactured by JASCO Corporation) and performing baseline correction using a standard reflector.
[0057] Standard reflector: Spectrolan (registered trademark) Measurement wavelength range: 380-780nm Measurement mode: %R Data capture interval: 0.5 nm UV / Vis Bandwidth: 5.0nm Response: Fast Scanning speed: 1000nm / min Light source:WI Specular reflection: Included Filter switching: Step The measured density of the sintered body of this embodiment is 5.8 g / cm 3 or more than 5.9g / cm 3 The upper limit of the measured density of the sintered body of this embodiment is 6.3 g / cm3 Less than or equal to 6.2g / cm 3 The specific measured density of the sintered body of this embodiment is 5.8 g / cm 3 More than 6.3g / cm 3 Less than or equal to 5.9g / cm 3 More than 6.2g / cm 3 The following is preferred:
[0058] In this embodiment, the measured density of the sintered body may be determined by a method conforming to JIS R 1634: 1998. That is, the measured density may be determined as the mass of the sintered body determined by mass measurement relative to the volume of the sintered body determined by Archimedes' method.
[0059] The shape of the sintered body of the present embodiment may be, for example, at least one selected from the group consisting of a sphere, an approximately sphere, an ellipse, a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, and an approximately polyhedron. Furthermore, any shape may be used depending on the purpose, such as various uses.
[0060] The sintered body of this embodiment may have a three-point bending strength of 800 MPa or more, or 900 MPa or more, and 1300 MPa or less, or 1200 MPa or less. Preferred three-point bending strengths include 800 MPa or more and 1300 MPa or less, or 900 MPa or more and 1200 MPa or less.
[0061] The three-point bending strength can be measured by a three-point bending test according to JIS R 1601. The measurement is performed 10 times, and the average value is taken as the three-point bending strength. The measurement can be performed using a columnar sintered body sample with a width of 4 mm and a thickness of 3 mm, with the distance between supports set to 30 mm.
[0062] The method for producing the sintered body of this embodiment is arbitrary. A preferred method for producing the sintered body of this embodiment is Contains a cerium source, an aluminum source, an yttrium-containing zirconia source, and a color-matching element source; CEO 2 The converted cerium content is 1.5 mol% or more and 6.0 mol% or less, Al2 O 3 The converted aluminum content is 0.05 mol% or more and 4.0 mol% or less, Y 2 O 3 The converted yttrium content is 2.0 mol% or more and 6.0 mol% or less, and The content of the color-changing element calculated as an oxide is more than 0 mol% and not more than 4.0 mol%, The color-tuning element source is a rare earth element other than yttrium and cerium, and an alkaline earth element A compound containing at least one of the following metal elements: Tetravalent zirconium (Zr 4+ a molding step of molding the powder composition to obtain a molded body, the ratio of the ion radius of the color-changing element to the ion radius of the color-changing element being more than 1.0 and not more than 1.6; a step of sintering the compact under atmospheric pressure to obtain a primary sintered body; and a secondary sintering step of sintering the primary sintered body in a reducing atmosphere; A method for producing a sintered body comprising the steps of:
[0063] The powder composition can be obtained by mixing a cerium source, an aluminum source, an yttrium-containing zirconia source, and a color-tuning element source. The cerium source, the aluminum source, the yttrium-containing zirconia source, and the color-tuning element source may have the same composition as the target sintered body, and each starting material may be contained as a powder.
[0064] The cerium source may be at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, halides, sulfates, acetates, and nitrates containing cerium, and is preferably at least one selected from the group consisting of oxides, hydroxides, oxyhydroxides, and chlorides, more preferably at least one selected from the group consisting of oxides, hydroxides, and chlorides, and even more preferably an oxide.
[0065] The cerium source may be a powder, and the average particle size is preferably 3.0 μm or less, 2.0 μm or less, or 1.0 μm or less, and more preferably 0.01 μm or more, 0.05 μm or more, or 0.1 μm or more. Examples of the combination of the upper and lower limits of the average particle size of the cerium source include 0.01 μm or more and 3.0 μm or less, 0.05 μm or more and 2.0 μm or less, and 0.1 μm or more and 1.0 μm or less.
[0066] The purity of the cerium source is preferably 99.0% by mass or more, and more preferably 99.9% by mass or more.
[0067] The aluminum source was alumina (Al 2 O 3 ) and at least one powder of an aluminum compound which is a precursor thereof, and examples thereof include at least one type of the group consisting of alumina, aluminum hydroxide, aluminum nitrate, and aluminum chloride, with alumina being preferred and α-alumina being more preferred.
[0068] The average particle size of the aluminum source is preferably 1.0 μm or less, 0.7 μm or less, or 0.5 μm or less, and more preferably 0.01 μm or more, 0.05 μm or more, or 0.1 μm or more. Examples of combinations of the upper and lower limits of the average particle size of the aluminum source include 0.01 μm or more and 1.0 μm or less, 0.05 μm or more and 0.7 μm or less, and 0.1 μm or more and 0.5 μm or less.
[0069] The purity of the aluminum source is preferably 99.0% by mass or more, and more preferably 99.9% by mass or more.
[0070] The yttrium-containing zirconia source is preferably zirconia containing 2.0 mol % or more and less than 6.0 mol % of yttrium.
[0071] The BET specific surface area of the yttrium-containing zirconia source is 5 m 2 / g or more 20m 2 / g or less, and even 5m 2 / g or more 17m 2 / g or less. The zirconia crystal phase of the stabilizing element-containing zirconia source preferably contains at least tetragonal crystals in the crystal structure of the zirconia, and the proportion of tetragonal crystals in the crystal structure is preferably 50% or more.
[0072] The purity of the yttrium-containing zirconia source is preferably 99.6% by mass or more, and more preferably 99.8% by mass.
[0073] The yttrium-containing zirconia source may contain at least one of an yttrium source and a zirconia source in addition to or instead of the yttrium-containing zirconia.
[0074] The yttrium source may be one or more selected from the group consisting of yttrium, yttrium hydroxide, and yttrium chloride, preferably at least one of yttrium and yttrium chloride, and more preferably yttrium. The zirconia source includes at least one of zirconia and zirconium hydroxide, preferably zirconia.
[0075] The color-changing element source may be one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, halides, sulfates, acetates, and nitrates containing the color-changing element, and is preferably one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, and chlorides, more preferably one or more selected from the group consisting of oxides, hydroxides, and chlorides, and even more preferably an oxide.
[0076] The purity of the color-tuning element source powder is preferably 98.0% by mass or more.
[0077] The color-changing element contained in the color-changing element source is preferably one or more selected from the group consisting of calcium, magnesium, erbium, holmium, dysprosium, terbium, gadolinium, europium, samarium, neodymium, praseodymium, and lanthanum, more preferably one or more selected from the group consisting of calcium, magnesium, erbium, gadolinium, europium, neodymium, and lanthanum, further preferably at least one of neodymium and lanthanum, and even more preferably lanthanum.
[0078] The powder composition preferably contains the above-mentioned starting materials in a homogeneous state.
[0079] The method for producing the powder composition may be any method as long as the starting materials are homogenized. A preferred method for producing the powder composition includes a mixing step by one or more methods selected from the group consisting of wet mixing, ball mill mixing, and stirring mill mixing, and preferably a mixing step by ball mill mixing.
[0080] The ball mill mixing is preferably a method in which a slurry obtained by mixing the powder composition with either water or alcohol is pulverized and mixed.
[0081] Any method may be used for drying the slurry, but one or more methods selected from the group consisting of static drying, spray drying using a two-fluid nozzle, and spray drying using an atomizer system are preferred.
[0082] After the mixing step, a granulation step may be performed in which the obtained powder composition is granulated. The granulation of the powder composition may be performed by any method that results in a slow aggregation of the powder, and an example of the method is spray granulation.
[0083] In the compacting step, the powder composition is compacted to obtain a compact.
[0084] The molding method in the molding step may be any method capable of molding the powder composition into a desired shape. Examples of the molding method include one or more methods selected from the group consisting of uniaxial pressing, cold isostatic pressing, slip casting, and injection molding, and at least one of uniaxial pressing and cold isostatic pressing. The molded body may have any shape that takes into consideration the shape of the desired sintered body and the thermal shrinkage caused by sintering. Examples of the shape of the molded body include one or more shapes selected from the group consisting of disk-shaped, columnar, plate-shaped, spherical, and approximately spherical.
[0085] In the primary sintering step, the compact obtained in the molding step is sintered under atmospheric pressure to obtain a primary sintered body.
[0086] The sintering temperature is preferably 1400°C or higher and 1600°C or lower, and more preferably 1500°C or higher and 1600°C or lower.
[0087] The firing atmosphere is an oxidizing atmosphere, preferably an air atmosphere.
[0088] The sintering time may be appropriately adjusted depending on the size of the molded body to be subjected to the primary sintering step and the characteristics of the sintering furnace, and may be, for example, from 2 hours to 6 hours, or from 2 hours to 4 hours. In the secondary sintering step, the primary sintered body obtained in the primary sintering step is sintered in a reducing atmosphere.
[0089] The sintering temperature is preferably 1300°C or higher and 1500°C or lower, and more preferably 1400°C or higher and 1500°C or lower.
[0090] The reducing atmosphere may be, for example, a mixed atmosphere of a reducing gas and an inert gas. The mixing ratio of the reducing gas and the inert gas in the reducing atmosphere is preferably such that the volume ratio of the reducing gas is 3% or more and 10% or less, more preferably 5% or more and 10% or less.
[0091] The reducing gas is preferably at least one of hydrogen and carbon monoxide, more preferably hydrogen. The inert gas is preferably at least one of nitrogen and argon, more preferably argon. The reducing atmosphere is preferably a mixed atmosphere of hydrogen and argon.
[0092] The sintering time may be appropriately adjusted depending on the size of the primary sintered body to be subjected to the secondary sintering step and the characteristics of the sintering furnace, and may be, for example, from 1 hour to 6 hours, or from 1 hour to 4 hours.
[0093] The secondary sintering step may be a known method, such as one or more selected from the group consisting of pressure sintering, vacuum sintering, and atmospheric sintering. The secondary sintering step is preferably atmospheric sintering, since it is simple and easy to apply industrially. In addition, the secondary sintering step is preferably not performed with sintering other than atmospheric sintering, and is preferably not performed with a pressure sintering step.
[0094] The manufacturing method of this embodiment may include at least one of a polishing step of polishing the sintered body and a processing step of processing the shape. The polishing step polishes the surface of the sintered body after sintering. By polishing, the sintered body can be made to have a surface state suitable for the intended use, such as imparting a glossy feel to the surface. The processing step processes the sintered body into an arbitrary shape. This allows the sintered body to have a shape according to the use. Either the polishing step or the processing step may be performed first. EXAMPLES
[0095] The present disclosure will be specifically described below with reference to examples. However, the present disclosure is not limited to these examples. (Actual density measurement) The measured density of the sintered body was determined by the method described in JIS R 1634: 1998. That is, the mass of the sintered body determined by mass measurement relative to the volume of the sintered body determined by Archimedes' method was calculated as the measured density of the sintered body. (Color Tone Measurement) The color tone of the sintered body sample was measured according to the method of JIS Z8722. For the measurement, a general spectrophotometer (device name: CM-700d, manufactured by Konica Minolta Japan, Inc.) was used. The measurement conditions were as follows, and the color tone was measured using the SCI method, which measures specular reflected light in addition to diffuse reflected light.
[0096] Light source: D65 light source Viewing angle: 10° Measurement method: SCI Background: Black background Measurement sample: (sample thickness) 2.4±0.1mm (Measured surface roughness) Ra≦0.02μm The sintered body samples used were sintered bodies having a thickness of 2.4±0.1 mm and one side mirror-polished to a measured surface roughness Ra≦0.02 μm, and the surfaces were measured. (Reflectance measurement) The reflectance was measured using an ultraviolet-visible-near infrared spectrophotometer (instrument name: V-670, manufactured by JASCO Corporation) and a dedicated integrating sphere unit was used to irradiate the sample with light generated from a light source (deuterium lamp and halogen lamp). The sintered sample was a sintered body with a thickness of 2.4±0.1 mm and one side mirror-polished to a measurement surface roughness Ra≦0.02μm, and the surface was measured. The measurement conditions were as follows:
[0097] Integrating sphere unit: ILV-724 (150mmφ) Photometric mode: %R Measurement range: 380nm ~ 780nm Data capture interval: 0.5 nm Bandwidth: 5.0 nm Response: Fast Scanning speed: 1000nm / min Light source: automatic Light source switching wavelength: 340.0nm Filter switching: Step Baseline correction: Baseline (Measurement of crystal phase) The crystal phase was identified by XRD measurement using an X-ray diffraction apparatus (apparatus name: Ultima IV, manufactured by RIGAKU Corporation) under the following conditions.
[0098] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 2° / min Measurement range: 2θ=26°~76° Acceleration voltage / current: 40mA / 40kV Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm The crystal phase was identified by smoothing and background removal processing using the analysis program attached to the X-ray diffractometer (program name: Integrated Powder X-ray Analysis Software PDXL Ver.2.2, manufactured by RIGAKU Corporation), and profile fitting the processed XRD pattern using a divided pseudo-Voigt function. The cubic crystal fraction was calculated from the XRD pattern of the sintered body surface using the above formula. The sintered body sample used was a sintered body that was mirror-polished on one side to have a thickness of 2.4±0.1 mm and a measured surface roughness Ra≦0.02 μm. (Three-point bending strength) The three-point bending strength was measured by a three-point bending test according to JIS R 1601. The measurement was performed 10 times, and the average value was taken as the three-point bending strength. The measurement was performed using a columnar sintered body sample with a width of 4 mm and a thickness of 3 mm, with the distance between supports set to 30 mm.
[0099] Example 1 47.26 g of 3.0 mol% yttrium-containing zirconia (TZ-3YS, manufactured by Tosoh Corporation), 2.50 g of cerium oxide (purity: 99.9%, average particle size: 0.8 μm), 0.12 g of calcium oxide (purity: 98% or more), and 0.12 g of aluminum oxide powder (purity: 99.9% or more, average particle size: 0.3 μm, roughly spherical) were mixed with pure water to obtain a mixed powder having the following composition. The mixing was performed by wet mixing in a ball mill using zirconia balls with a diameter of 10 mm as the grinding medium for 24 hours. After mixing, the mixture was dried in an air atmosphere at 110 ± 15 ° C for 18 hours to obtain a raw material powder having the following molar composition.
[0100] CEO 2 : 3.7mol% CaO: 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) (Primary sintering) The raw powder was filled into a cylindrical mold and uniaxially pressed at a pressure of 98 MPa to obtain a cylindrical compact with a diameter of 25 mm and a thickness of 3.6 mm. The obtained compact was sintered in a muffle furnace at a heating rate of 100°C / hour in air at 1550°C for 2 hours for primary sintering, and then cooled to room temperature at a heating rate of 200°C / hour to obtain a primary sintered compact. The obtained primary sintered compact exhibited a yellow color derived from tetravalent cerium. (Secondary sintering) The primary sintered body was placed in a tubular furnace equipped with an alumina furnace tube with an inner diameter of 50 mm, an outer diameter of 60 mm, and a total length of 100 mm, and sintered at 1450°C for 1 hour in a reducing atmosphere with a heating rate of 500°C / hour to obtain a sintered body, which was used as the sintered body of this example. The reducing atmosphere was a hydrogen-argon flow atmosphere (flow rate: 1 L / min) using hydrogen (5%)-argon (95%) gas. The sintered body of this example was red in color. The sintered body of this example also contained tetragonal and cubic crystals in its crystal structure.
[0101] Example 2 The sintered body of this example was obtained in the same manner as in Example 1, except that magnesium oxide (purity: 98% or more) was used instead of calcium oxide to obtain a mixed powder having the following molar composition. The sintered body of this example had a spinel ratio of 0.
[0102] CEO 2 : 3.7mol% MgO: 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 3 The sintered body of this example was obtained in the same manner as in Example 1, except that strontium oxide (purity: 99.9% or more) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0103] CEO 2 : 3.7mol% SrO: 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 4 The sintered body of this example was obtained in the same manner as in Example 1, except that scandium oxide (purity 99.9%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0104] CEO 2 : 3.7mol% Sc 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 5 The sintered body of this example was obtained in the same manner as in Example 1, except that lutetium oxide (purity 99.5%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0105] CEO 2 : 3.7mol% Lu 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 6 The sintered body of this example was obtained in the same manner as in Example 1, except that erbium oxide (purity 99.99%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0106] CEO 2 : 3.7mol% Er 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 7 The sintered body of this example was obtained in the same manner as in Example 1, except that gadolinium oxide (purity 99.9%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0107] CEO 2 : 2.2mol% Gd 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2O 3 Contains ZrO 2 : Remainder (97.0mol%) Example 8 The sintered body of this example was obtained in the same manner as in Example 1, except that neodymium oxide (purity 99.9%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0108] CEO 2 : 3.7mol% Nd 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 9 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0109] CEO 2 : 3.7mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 10 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0110] CEO 2 : 3.7mol% La 2 O 3 : 1.0mol% Al 2 O3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.0mol%) Example 11 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition. The three-point bending strength of this example was 999 MPa.
[0111] CEO 2 : 3.8mol% La 2 O 3 : 1.0mol% Al 2 O 3 : 1.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (93.9mol%) Example 12 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0112] CEO 2 : 3.9mol% La 2 O 3 : 2.0mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (93.8mol%) Example 13 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0113] CEO2 : 3.8mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 0.1mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.6mol%) Example 14 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0114] CEO 2 : 3.7mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 1.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (94.5mol%) Example 15 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0115] CEO 2 : 3.7mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 2.5mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (93.3mol%) Example 16 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0116] CEO 2 : 2.2mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (97.0mol%) Example 17 The sintered body of this example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0117] CEO 2 : 4.9mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (94.3mol%) Example 18 A hydrated zirconia sol was obtained by hydrolyzing an aqueous solution of zirconium oxychloride. Yttria (Y 2 O 3 ) was added to the hydrated zirconia sol, which was then dried and calcined at 1160°C for 2 hours to obtain calcined zirconia powder containing yttria (specific surface area 5 m 2The calcined powder thus obtained was washed with distilled water and then dried at 110°C to obtain a zirconia powder containing 2.5 mol% yttria. The sintered body of this example was obtained in the same manner as in Example 1, except that the zirconia powder containing 2.5 mol% yttria and lanthanum oxide (purity 99.9%) were used instead of calcium oxide to obtain a mixed powder having the following molar composition.
[0118] CEO 2 : 3.7mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 2.5mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.5mol%) Example 19 Zirconia containing 4.0 mol% yttria (Tosoh Corporation, TZ-4YS; specific surface area 7 m 2 The sintered body of this example was obtained in the same manner as in Example 1, except that a lanthanum oxide powder (purity 99.9%) was used instead of calcium oxide and that the mixed powder had the following molar composition. CEO 2 : 3.8mol% La 2 O 3 : 0.5mol% Al 2 O 3 : 0.3mol% 4mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.4mol%) Comparative Example 1 The sintered body of this comparative example was obtained in the same manner as in Example 1, except that aluminum oxide was not used, lanthanum oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0119] CEO 2: 3.8mol% La 2 O 3 : 0.5mol% (Al 2 O 3 : 0.0 mol%) 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.7mol%) Comparative Example 2 Calcium oxide was not used, and zirconia powder containing 4.0 mol% yttria (TZ-4YS, manufactured by Tosoh Corporation; specific surface area 7 m) was used. 2 The sintered body of this comparative example was obtained in the same manner as in Example 1, except that a sintered body of this comparative example was obtained using 100% sintered body powder (0.1 g / g, purity 99.8% or more) and that the mixed powder had the following molar composition.
[0120] CEO 2 : 3.8mol% Al 2 O 3 : 0.3mol% 4mol%Y 2 O 3 Contains ZrO 2 : Remainder (95.9mol%) Comparative Example 3 A sintered body of this comparative example was obtained in the same manner as in Example 1, except that niobium oxide (purity 99.9%) was used instead of calcium oxide, and the mixed powder had the following molar composition.
[0121] CEO 2 : 2.2mol% Nb 2 O 5 : 0.5mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (97.0mol%) In addition, the mixed powder and sintered body of Nb 2 O 5The content was calculated by the following formula based on the measurement method for the color-changing element content. Nb 2 O 5 Content [mol%] ={(Nb 2 O 5 ) / (ZrO 2 +Y 2 O 3 +CeO 2 +Al 2 O 3 +Nb 2 O 5 )}×100 The ionic radius ratio of niobium (Nb) to Zr is 0.74 Å (Nb 5+ ) and the ionic radius ratio to Zr was calculated in the same manner as for other color-matching elements, and found to be 0.88 (Nb 5+ / Zr 4+ ) was. Comparative Example 4 A sintered body of this comparative example was obtained in the same manner as in Example 1, except that lanthanum oxide (purity 99.9%) was used instead of calcium oxide to obtain a mixed powder having the following molar composition. CEO 2 : 3.7mol% La 2 O 3 : 4.1mol% Al 2 O 3 : 0.3mol% 3mol%Y 2 O 3 Contains ZrO 2 : Remainder (91.9mol%)
[0122] [Table 1]
[0123] [Table 2]
[0124] [Table 3]
[0125] In all of the sintered bodies of Examples 1 to 19, 2.0≦a * / b * And 2.4≦R 700 / R 600 It was confirmed that the color exhibited a vivid red color under daylight.
[0126] In addition, Al 2 O 3 Compared with Comparative Examples 1 and 2 which do not contain * / b * and R 700 / R 600 It was confirmed that the sintered body had a high value of Al, and exhibited a vivid red color under daylight while suppressing the orange color. 2 O 3 In contrast to Comparative Example 3, which contains but does not contain a color-matching element, the embodiment * / b * and R 700 / R 600 It was confirmed that the sintered body of Comparative Example 3 had a high value of 0.01 and exhibited a vivid red color under daylight while suppressing the orange color. * / b * and R 700 / R 600 The value of a was lower than that of the sintered bodies of Examples 1 to 19. In Comparative Example 4, in which the content of the color-tuning element exceeded 4 mol%, * / b * and R 700 / R 600 The value was low, and no sintered body exhibiting a vivid red color was obtained. [Industrial Applicability]
[0127] The zirconia sintered body of the present invention is a sintered body with excellent aesthetics, and can be used for various components such as scratch-resistant, high-quality jewelry and decorative members, for example, watch components and exterior components of portable electronic devices.
Claims
1. Contains cerium, aluminum, yttrium, and color-matching elements; CeO 2 The converted cerium content is 1.5 mol% or more and 6.0 mol% or less, A 2 O 3 The converted aluminum content is 0.05 mol % or more and 4.0 mol % or less, Y 2 O 3 The converted yttrium content is 2.0 mol% or more and 6.0 mol% or less, and The content of the color-tuning additive element calculated as an oxide is more than 0 mol % and not more than 4.0 mol %, The cerium is trivalent cerium (Ce 3+ ), The color-changing element is at least one element selected from the group consisting of rare earth elements other than yttrium and cerium and alkaline earth metal elements, and Tetravalent zirconium (Zr 4+ The ratio of the ionic radius of the color-changing element to the ionic radius of the color-changing element is more than 1.33 and not more than 1.
40. Zirconia sintered body.
2. The sintered body according to claim 1 , wherein the zirconia has a crystal structure including tetragonal and cubic crystals.
3. 3. The sintered body according to claim 1, wherein the color-tuning element is one or more selected from the group consisting of calcium, magnesium, erbium, holmium, dysprosium, terbium, gadolinium, europium, samarium, neodymium, praseodymium, and lanthanum.
4. L * a * b * In the color system, hue b * Hue a * The ratio (a * / b * ) is 2.0≦(a * / b * 3. The sintered body according to claim 1 or 2,
5. Reflectance for light at a wavelength of 700 nm (R 700 ) and the reflectance (R 600 ) ratio (R 700 / R 600 ) is 2.4≦(R 700 / R 600 3. The sintered body according to claim 1 or 2,
6. 3. The sintered body according to claim 1, wherein the ratio of the height of the peak top at 2θ=37.0±0.3 to the height of the peak top at 2θ=30.0±0.3 in an XRD pattern is 0.005 or less.
Citation Information
Patent Citations
Colored zirconia sintered body and its producton
JP1987059571A
Manufacture of colored zirconia sintered body
JP1987083366A
Zirconia composite sintered compact and biomaterial using the same
JP2006104024A
Red light transmitting zirconia sintered body and method for producing the same
JP2011207745A
Red zirconia sintered body and method for producing the same
JP2017075086A